2015
DOI: 10.1186/s13002-015-0057-8
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and use of medicinal plants during pregnancy among women at health care centers in three regions of Mali, West-Africa

Abstract: BackgroundAlthough, medicinal plants have been important for women’s health historically, the knowledge about such use during pregnancy in developing countries is limited. This is the first quantitative, ethnobotanical study on Malian women’s use of and attitudes towards the use of medicinal plants during pregnancy.The aim of the study was to describe Malian women’s use of medicinal plants during pregnancy according to indications and to evaluate the potentially safety of such use. The overall aim was to prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
5
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 34 publications
3
50
5
4
Order By: Relevance
“…This difference can be due to inter cultural and accessibility variance of herbal medicine across countries which influence their use. Also our current finding of herbal medicine use lower than a study conducted in Mali were 79.9.% use herbal medicine (17). This variation might occurs due to disease prevalence between the study areas since malaria symptoms is common in Mali study which encourage use of medicinal plants to treat malaria.…”
Section: Socio-demographic Characteristics Of Study Participantscontrasting
confidence: 52%
“…This difference can be due to inter cultural and accessibility variance of herbal medicine across countries which influence their use. Also our current finding of herbal medicine use lower than a study conducted in Mali were 79.9.% use herbal medicine (17). This variation might occurs due to disease prevalence between the study areas since malaria symptoms is common in Mali study which encourage use of medicinal plants to treat malaria.…”
Section: Socio-demographic Characteristics Of Study Participantscontrasting
confidence: 52%
“…No particular trends have been revealed by researchers (Nordeng and Havnen, 2004;Rahman et al, 2008;Tabatabaee, 2011;Tang et al, 2016). In some cases, the women simply continued using the herbal products until they "felt better" (Nergard et al, 2015).…”
Section: Consumption Of Hms By Pregnant Womenmentioning
confidence: 99%
“…84 TCAM users were also found to be younger (<30 years) 84 98 and married 84 98 compared with non-TCAM users. 24 Meanwhile, three studies from Zambia, 82 Mali 90 and Ethiopia 83 reported no sociodemographic difference between TCAM users and non-users. With regard to TCAM use during childbirth, two studies drawn from a large sample of Nigerian women show TCAM users are likely to be women who are less educated, from low socioeconomic background, Muslim and primiparous.…”
Section: Prevalence Of Concurrent Use Of Tcam and Allopathic Medicinesmentioning
confidence: 99%